A Composite Girder System for Joist Supported Slabs - Rongoe, James (Engineering Journal, 1984)
In current practice composite action between the concrete slab and the girder is not taken advantage of when framing a floor using standard open web joists and continuous metal decking. The reason is the girder is depressed (usually 2.5 in.) to receive the joist seat and therefore is not in direct contact with the concrete slab. Since the girder supporting the joists is noncomposite, the economic and other advantages of composite design are not realized. Also, because the girder is not framed flush with the joists, its bottom flange is usually a critical element in setting floor-to-floor heights and clearances for duct work. This paper describes a novel composite girder system to be used in conjunction with joist supported slab systems. As shown in Fig. 1, at the heart of the system are connections, such as tees, which are welded to the top flange of the girder intermittently between the joist locations. (These pieces are analogous to stubs in a stub-girder system). The tops of these connections are flush with the bottom of the slab and thus provide a surface to which standard shear connectors can be attached. The former gap between the bottom of deck and top of girder can now be utilized structurally.